The impact of anti-Muslim hostilities on how Muslims connect their religiosity to support for gender equality in Western Europe - Glas, Saskia; Spierings, Niels (Frontiers in Political Science, 2022)
Right-wing populist voices argue that Muslims do not belong in Western Europe because Islam opposes the “core Western value” of women's empowerment. Ironically, such hostilities could cause European Muslims to reject antagonistic natives and their “Western values,” potentially creating backlashes in Muslims' support for gender equality. Delving into this possibility, this study diverges from simple conceptualizations of one inherently patriarchal Islam to study the diversity among Muslims in the gendered meanings they attach to their religion in different contexts. Empirically, we use a uniquely pooled dataset covering over 9,000 European Muslims in 16 Western European countries between 2008 and 2019. Multilevel models show that while mosque attendance limits support for public-sphere gender equality, religious identifications only do so among men and individual prayer only among women. Additionally, our results tentatively indicate that in more hostile contexts, prayer's effects become more patriarchal while religious identification's connection to opposition to gender equality weakens. We conclude that Islamic religiosities shape Muslims' support for public-sphere gender equality in far more complex ways than any right-wing populist claim on one essential patriarchal Islam captures.